No Consistent Evidence for Between- and Within-Person Associations Between Objective Social Media Screen Time and Body Image Dissatisfaction: Insights From a Daily Diary Study - Adalia Y. H. Goh; Andree Hartanto; K. T. A. Sandeeshwara Kasturiratna; Nadyanna M. Majeed (Social Media + Society)
With the abundance of social media content that promotes unrealistic beauty standards, there are growing concerns about the potential negative impact of social media use on body image satisfaction. While some studies highlight negative associations, others present null effects, pointing to methodological limitations like biased and unreliable self-reported screen time measures and a focus on singular platforms. Addressing these gaps, our study employed a daily diary method to objectively measure social media screen time across six major platforms ( Twitter , Reddit , TikTok , YouTube , Instagram , and Facebook ), alongside daily body image dissatisfaction among 252 young adults ( M age  = 21.67 years, 67.77% female) over 7 days. Through multilevel modeling, our analysis revealed no significant within- or between-person associations between social media screen time and body image dissatisfaction, a finding consistent across all platforms. In addition, the lack of association between social media screen time and body image dissatisfaction was consistent across several exploratory moderators such as sex, self-esteem, and perfectionistic self-presentation. The current study did not find strong evidence supporting the concerns surrounding the potential detrimental link between social media screen time and body image dissatisfaction.